2013 IEEE International Conference on Robotics and Biomimetics (ROBIO) 2013
DOI: 10.1109/robio.2013.6739641
|View full text |Cite
|
Sign up to set email alerts
|

User evaluation of service robotic arms based on ICF through interviews with people with upper-limb disability

Abstract: The iArm is a service robot arm to help people with upper-limb disability in their daily lives. The iArm has been produced for about 10 years in the Netherlands. The National Institute of Advanced Industrial Science and Technology has developed RAPUDA (Robotic Arm for Persons with Upper-limb DisAbility). The effectiveness of the RAPUDA was evaluated by conducting ergonomics experiments. We analyze the effectiveness of the robot arm in daily life through interviews with iArm users living in the Netherlands and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(10 reference statements)
0
6
1
Order By: Relevance
“…The assessments that focused on ADLs and IADLs showed that users are able to successfully accomplish a variety of tasks with a robotic arm (Bach, Zeelenberg, & Winter, 1990; Chaves, Koontz, Garber, Cooper, & Williams, 2003; Clark, 2013; Gelderblom et al, 2001; Hammel, Van der Loos, & Perkash, 1992; Jardón, Gil, De La Peña, Monje, & Balaguer, 2011; Jardón, Monje, & Balaguer, 2012; Kim et al, 2012; Kwee, Quaedackers, Van de Bool, Theeuwen, & Speth, 1999; Maheu, Archambault, Frappier, & Routhier, 2011; Mahoney, 2001; Routhier & Archambault, 2010; Van der Loos et al, 1990; Wakita et al, 2013; Wakita, Yoon, & Yamanobe, 2012; Wang et al, 2013). For example, the use of a robotic arm allowed users to drink (Jardón et al, 2012; Wakita et al, 2013), to eat (Wakita et al, 2013), and to brush their teeth (Jardón et al, 2012). Therefore, many authors concluded that robotic arms have the potential to increase users’ independence (Chaves et al, 2003; Clark, 2013; Gelderblom et al, 2001; Hammel et al, 1989; Jardón et al, 2011, 2012; Seamone & Schmeisser, 1985; Topping & Smith, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessments that focused on ADLs and IADLs showed that users are able to successfully accomplish a variety of tasks with a robotic arm (Bach, Zeelenberg, & Winter, 1990; Chaves, Koontz, Garber, Cooper, & Williams, 2003; Clark, 2013; Gelderblom et al, 2001; Hammel, Van der Loos, & Perkash, 1992; Jardón, Gil, De La Peña, Monje, & Balaguer, 2011; Jardón, Monje, & Balaguer, 2012; Kim et al, 2012; Kwee, Quaedackers, Van de Bool, Theeuwen, & Speth, 1999; Maheu, Archambault, Frappier, & Routhier, 2011; Mahoney, 2001; Routhier & Archambault, 2010; Van der Loos et al, 1990; Wakita et al, 2013; Wakita, Yoon, & Yamanobe, 2012; Wang et al, 2013). For example, the use of a robotic arm allowed users to drink (Jardón et al, 2012; Wakita et al, 2013), to eat (Wakita et al, 2013), and to brush their teeth (Jardón et al, 2012). Therefore, many authors concluded that robotic arms have the potential to increase users’ independence (Chaves et al, 2003; Clark, 2013; Gelderblom et al, 2001; Hammel et al, 1989; Jardón et al, 2011, 2012; Seamone & Schmeisser, 1985; Topping & Smith, 1999).…”
Section: Resultsmentioning
confidence: 99%
“…It was estimated that the average time per day spent on ADLs and IADLs could be reduced by 1.31 hr (Maheu et al, 2011) to 3 hr (Bach et al, 1990). Concerning users’ satisfaction, results of the included studies showed that modifications or improvements in existing robotic arms are needed to better meet their users’ needs (Bach et al, 1990; Busnel et al, 1999; Cammoun, Detriche, Lauture, & Lesigne, 1993; Clark, 2013; Grigorescu, Lüth, Fragkopoulos, Cyriacks, & Gräser, 2012; Hall, Glass, Hammel, Leifer, & Perkash, 1987; Hammel et al, 1989, 1992; Hillman, 1987; Jardón et al, 2011, 2012; Kim et al, 2010, 2012; Kwee et al, 1983, 1999; Kwee, Quaedackers, Van De Bool, Theeuwen, & Speth, 2002; Seamone & Schmeisser, 1985; Topping & Smith, 1999; Wakita et al, 2013; Wang et al, 2013). For example, in a study evaluating the ASIBOT robot, participants suggested several changes to make it more useful, such as reducing its size, incorporating a voice recognition system, adding tasks, and improving safety conditions (Jardón et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to our results, previous researches suggest that the use of a robotic arm indeed increases independence and decreases human assistance needed. 37,38 Römer et al 37 reported that iARM users performed 40% more tasks by themselves and needed 30% less human assistance than nonusers with similar disabilities. A similar decrease in human assistance was observed in a 1-year prospective study with new users.…”
Section: Impacts Of the Jaco Robotic Armmentioning
confidence: 99%
“…31 Comparable results were obtained with iARM users. 37,38 This overview shows that research is still limited on the impacts of robotic arms in improving independent living and social participation of individuals with upper-limb disabilities, and several knowledge gaps remain. First, given the versatility of robotic arms, it is expected that their benefits will evolve over a period of several weeks, so that the participants can have the needed time to familiarize themselves with the device, learn to use it, and adopt it.…”
mentioning
confidence: 99%
“…We carried out interviews with iArm users and participants in the RAPUDA experiments [10] (Figure 3 and 4). We have evaluated the effectiveness of the robot arm for use in daily life on the basis of ICF performance ratings.…”
Section: B Evaluation Of Robot Arm For Upper-limb Disabilitymentioning
confidence: 99%